2013
DOI: 10.3109/08820538.2012.760615
|View full text |Cite
|
Sign up to set email alerts
|

Phakic Cystoid Macular Edema Secondary to Idiopathic Macular Telangiectasia Type 1 Responsive to Topical Anti-Inflammatory Agents

Abstract: Topical steroidal and non-steroidal anti-inflammatory agents may lead to long-term resolution of cystoid macular edema secondary to idiopathic macular telangiectasia type 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to this case and previous studies [1][2][3]5], it seems bilateral involvement and female sex cannot rule out the diagnosis of type 1 IMT. Moreover, typical features of type 1 IMT in fundus examination may not be seen in all cases and we should consider other modalities like FA and OCTA alongside fundus examination for making the proper diagnosis.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…According to this case and previous studies [1][2][3]5], it seems bilateral involvement and female sex cannot rule out the diagnosis of type 1 IMT. Moreover, typical features of type 1 IMT in fundus examination may not be seen in all cases and we should consider other modalities like FA and OCTA alongside fundus examination for making the proper diagnosis.…”
Section: Discussionmentioning
confidence: 55%
“…In Gass and Blodi's study [ 1 ], telangiectasia was present bilaterally in 1 male case among 8 patients of IMT. Finally, Dunn et al [ 5 ] also reported a male patient with bilateral type 1 IMT complicated by cystoid macular edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, topical NSAIDs together with topical steroids may lead to long-term resolution of cystoid macular edema secondary to idiopathic macular telangiectasia type 1. 17 …”
Section: Discussionmentioning
confidence: 99%